Countrywide screening of spatiotemporal overlap between coastal and marine recreation and waterbirds in Denmark. (September 2021) - Laursen, Karsten; Kaae, Berit C.; Bladt, Jesper; Skov-Petersen, Hans; Clausen, Preben; Olafsson, Anton Stahl; Draux, Hélène; Bregnballe, Thomas
Abstract: Coastal zones are important for recreational activities and waterbirds. However, recreational activities may have negative implications for birdlife, which calls for balancing of both types of use by integrated coastal and marine planning and management. Successful integrated management and planning require spatiotemporal knowledge about the species needing protection and the outdoor recreation activities. This paper examines water-oriented outdoor recreation in Denmark in terms of activities, seasonality and geographical distribution, and presents a national screening of spatiotemporal overlap between coastal and marine recreational activities and waterbirds based on 10, 291 responses and 6, 499 geographical positions. In total 77.6% of the Danish population participated in water-oriented outdoor recreation activities at least once within a year. The most frequent activities were to move along or stay on the coast/shore (63.9%), to bathe and swim (34.4%) and to observe nature and wildlife (20.3%). Overlap between recreation and waterbirds, representing potential conflicts, ranged from 0.8% in winter on water to 27.7% in summer on the coast. The results revealed significant negative effects between recreational activities and abundance of waterbirds during spring and summer on the water. The results also indicate that most recreational activities use areas with no or low densities of waterbirds. Successful coastal and marine planning requires application of management tools that include educational and interpretative initiatives to enhance coexistence. However, for detailed management, more studies are urgently needed of spatiotemporal patterns, adaptations, conflicts and coexistence between recreational activity and waterbirds. Management implications: The results support integrated planning and management of water-based recreation in conjunction with waterbirds by: - Providing spatially explicit year-round data on recreational and waterbird use of coastal and marine areas. - Obtaining the first ever national overview of potential areas of conflict and of possibilities for coexistence between coastal and marine recreation and waterbirds. - Identifying specific local areas in need of management action and more detailed studies of effects and impacts of coastal and marine recreation on waterbirds.